Visualising and revitalising traditional Chinese martial arts: Visitors' engagement and learning experience at the 300 years of Hakka Kungfu. Issue 2 (28th February 2019) - Lo, Patrick; Chan, Holly H.Y.; Tang, Angel W.M.; Chiu, Dickson K.W.; Cho, Allan; See-To, Eric W.K.; Ho, Kevin K.W.; He, Minying; Kenderdine, Sarah; Shaw, Jeffrey
Abstract : Purpose: The purpose of this paper is to examine how the emergent 3D interactive media technologies are used as a viable tool for enhancing visitors' overall experiences at an exhibition entitled, 300 Years of Hakka Kungfu – Digital Vision of Its Legacy and Future (Hakka Kungfu Exhibition) – presented and co-organized by the Intangible Cultural Heritage Office of Hong Kong, International Guoshu Association and the School of Creative Media, City University of Hong Kong. Design/methodology/approach: A questionnaire survey in both online and paper-based formats was used for identifying visitors' experiences in the interactions with the multimedia technologies. For this research study, a questionnaire, consisting of 26 items, was set out to measure the visitors' experiences at the Exhibition. Since the Exhibition was about presenting a centuries-old Chinese cultural heritage, Hakka Kungfu via the use multimedia technologies, in the context of establishing a dialogue between the past and present, the researchers included questionnaire items that were devoted to enquire about the level of understanding, knowledge and enjoyment, and visitors' new knowledge about Hong Kong history and culture was successfully disseminated to the respondents at the end of the questionnaire. Findings: A total of 209 completed questionnaires were collected at this Hakka Kungfu Exhibition. The findings reveal that the exhibits did attract people at all ages. This Exhibition gave the visitors a sense of interest and wonder in the object and information presented in the Exhibition. Findings of this study also reveal that this Exhibition has successfully attracted a large number of female visitors, as well as visitors who have never taken any martial arts training. In addition, visitors' Exhibition experience was found to be memorable, as well as enjoyable. Furthermore, visitors' experience within the Exhibition suggested that it was entertaining, as well as educational. By creating a long-lasting impact on the minds of these Exhibition visitors about the connections between and relevance of traditional Chinese Kungfu, their collective cultural identity, as well as the contemporary society we live in. The Exhibition exemplified the successful integration of the presentation of Kungfu as a form of cultural heritage with engagement-creating technology, in which technology is unobtrusive but effective. Originality/value: Although it is already a global trend for the museums to integrate multimedia technologies into their exhibitions, research on the situation and feedback of multimedia technology used in the museum exhibitions in Hong Kong is scarce as well as scattered. Findings of this study could help identify various factors involved in audience participation, thereby exploring the possibility of building a contact point/space for traditional Chinese Kungfu as an intangible cultural heritage, via the integration of the latest media technologies. In particular, the development of multimedia technologies has become increasingly important to museums, and museum professionals have been exploring how digital and communication technologies can be developed to offer visitors a more interactive, personalized museum experience. In general, despite the growing interest in deploying digital technology as interpretation devices in museums and galleries, there are relatively few studies that examine how visitors, both alone and with others, use new technologies when exploring the museum contents.